1995
DOI: 10.1089/jir.1995.15.495
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-αElicits Downregulation of Human Papillomavirus 18 mRNA in HeLa Cells by Selective Repression of Endogenous Viral Transcription

Abstract: We have reported that interferon-alpha inhibits HPV-18 mRNA in HeLa cells. Here we examine mechanisms by which IFN could modulate HPV expression. In northern blot experiments, we observed that interferon-alpha 2b treatment reduced HPV-18 mRNA levels in a time- and dose-dependent manner, with a maximal effect achieved at 48 h. Simultaneously, induction of 2-5A synthetase mRNA was verified as indicative of IFN action. The IFN regulatory effect on HPV-18 mRNA at 48 h required de novo protein synthesis. We perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…IFN-␣ also inhibits HPV-16 E7 protein expression but not transcription and not E6 protein expression, suggesting that growth and transformation inhibition is mediated by an inhibition in E7 protein expression. Others (101,112) have shown that IFN-␣ inhibits transcription of HPV-18 E6 and E7 genes in HeLa cells, a cervical carcinoma cell line containing integrated HPV-18 DNA. Interestingly, this effect appears to be shared with IFN-␥ (101).…”
Section: School Of Medicine University Of California San Francisco mentioning
confidence: 99%
“…IFN-␣ also inhibits HPV-16 E7 protein expression but not transcription and not E6 protein expression, suggesting that growth and transformation inhibition is mediated by an inhibition in E7 protein expression. Others (101,112) have shown that IFN-␣ inhibits transcription of HPV-18 E6 and E7 genes in HeLa cells, a cervical carcinoma cell line containing integrated HPV-18 DNA. Interestingly, this effect appears to be shared with IFN-␥ (101).…”
Section: School Of Medicine University Of California San Francisco mentioning
confidence: 99%
“…Another study conducted on HeLa cells also suggested that 1 × 10 3 IU/mL IFN-α selectively inhibited cytoplasmic HPV 18 mRNA [68]. These results were confirmed by Perea et al, who even suggested that, as IFN-α did not affect HPV 18 transcripts stability nor did mediate its inhibitory effects through HPV 18 enhancer sequences, it could, however, possibly repress nascent viral transcripts through regulatory cellular flanking regions [69]. Nonetheless, our pilot data can open the way to further investigations on this HPV-specific active substance of 2LPAPI.…”
Section: Discussionmentioning
confidence: 67%
“…IFN also induces the MX proteins which directly interfere with viral replication (30). Both type I and II IFNs inhibit expression of E6 and E7 RNAs in HPV-immortalized cells (32)(33)(34)(35)(36)(37). IFN-alpha also inhibits immortalization of keratinocytes by HPV-16 (34).…”
Section: Interferonsmentioning
confidence: 99%